Online Competency Based Education Framework using Moodle LMS: A Case of HEIs in Kenya - Hadullo, Kennedy (International journal of education and development using information and communication technology, 2021)
The purpose of this study was to develop a Framework that can be used to implement an online Competency-based education (CBE) program using a Learning Management system such as Moodle. CBE refers to a system of instruction, assessment, grading, and academic reporting that is based on students demonstrating that they have the knowledge and skills they are expected to learn as they progress through their educational path. However, little is known regarding how an online supported CBE program can be planned, designed, and implemented, to ensure learners complete activities and thus develop competency. This study advances theoretical perspectives of CBE as steps taken towards the development of an online CBE Framework suitable for Higher Education Institutions (HEIs) in Kenya. The study found that: Planning (Technology Infrastructure, organization and program design and development); Design (competency standards, instructional design, content development, LMS installation and customization); Implementation (learning activities, Moodle competency framework, assessments, and discussion forums); Improvement (Moodle Analytics) and Achieving (attainment of competency) were the most influential factors in determining the successful implementation of an Online CBE program in HEIs.